Análise de meios filtrantes em filtros de mangas do processo de dessulfuração da siderurgia - Vieira, Ana Cristina Coelho (2024)
The emissions of ultrafine particles in the air are considered a global problem. The increase is linked to economic development and extensive urban expansion. These particles are inhalable, and exposure to them can cause various diseases or even lead to death. As a result, there has been a need to develop and optimize methods and equipment to control their emissions. In this context, bag filters stand out as one of the most commonly used filters due to their high filtration efficiency and stability. However, the filter medium used directly affects filtration efficiency, and how the filter medium is manufactured—such as needle felt and hydroentangled felt—also impacts efficiency and lifespan. Given the existing gap in the literature regarding the influence of filter medium manufacturing techniques on filtration efficiency and their impact in industrial settings, the objective of this research is to analyze and compare the filtration performance of filter media manufactured using needle felt and hydroentangled felt techniques, both virgin and with 3- and 4-year usage, in the bag filter system of the desulfurization process in the steel industry. The particulate material and filter media used were characterized to understand their behavior during filtration tests. Filtration tests were conducted using a test filter based on the VDI 3926 standard, with pulse-jet cleaning, evaluating collection efficiency and pressure drop evolution over 30 filtration cycles. The results of particulate material characterization showed that it is predominantly composed of calcium and iron, with a median aerodynamic diameter of 2.64 µm. The hydroentangled filter medium, along with a larger fiber diameter, exhibited lower thickness and permeability compared to the needle felt. Consequently, the penetration of particulate material into the hydroentangled medium was lower, facilitating the cleaning process of the filter bags and increasing filtration efficiency. After 30 filtration cycles, the used hydroentangled filter medium achieved an efficiency of approximately 99.9%, while the needle-felt filter medium reached approximately 99.7%. Regarding lifespan over the years, the 4-year-old filter bags showed greater residual pressure drop than the 3-year-old bags, as expected due to particle accumulation in the filter medium over time. However, the increase in residual pressure drop was smaller for the hydroentangled bags than for the needle-felt bags, resulting in a longer lifespan. Therefore, under the analyzed conditions, the hydroentangled filter medium demonstrated greater effectiveness, with a longer lifespan and lower residual pressure drop during filtration.